Research methods for interior design : applying interiority - Vaux, Dana E.; Wang, David, 1954- (New York, NY : Routledge, 2020)
"Interior design has shifted significantly in the past fifty years from a focus on home decoration within family and consumer sciences to a focus on the impact of health and safety within the interior environment. This shift has called for a deeper focus in design research. Research Methods for Interior Design provides a broad scope of research methods for interior design students from qualitative to quantitative emphases. Through four distinct sections, the authors not only lay out the theory of interiority-a subjective sense a person feels in his or her relation to a physical environment, which results in positive attachments of communal belonging-but also how designers can access interiority through a variety of research methodologies. Expanding beyond environments defined by physical walls, this book transcends the traditional discipline of interior design by foregrounding interiority as a theoretical conception. With case studies, exercises, study questions and recommended additional research projects and literature, this book hits the mark on the need for resources that inform and enrich the research process with a broader scope for interior design students, educators, and researchers"--
OCLC-licensed vendor bibliographic record.
Keywords: Interior decoration -- Research -- Methodology; ARCHITECTURE / General; ARCHITECTURE / Interior Design / General; ARCHITECTURE / Study & Teaching